(untitled) - Drucker, Peter F. (Oxford, 1997)
Drucker on Asia is written in two parts (Times of Challenge & Time to Reinvent) which is the result of a dialogue between Peter Drucker and Isao Nakauchi on international themes.
Keywords: Economic forecasting,Dự báo kinh tế; Asia,Châu Á